FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Hanifah Maharani; Dina Rahayuning Pangestuti; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Breastfeeding mothers are classified into nutrition vulnerable groups because of breast milk (ASI) is the mainfood for the baby that is obtained from their mother. Riskesdas 2007-2008 showedthat the risk of chronic energy deficiency breastfeeding mothers in Indonesia as much as 34.6%. This study aims to determine factors associated with the nutritional status of breastfeeding mothers. The study was the observational analytic with cross-sectional study design. The sample in this study is breastfeeding either exclusively or non-exclusively, have babies aged 0-6 months as many as 47 people with purposive sampling technique. The research instrument was a questionnaire and measures of nutritional status (digital scales, microtome, ribbon LILA). The statistical analysis used was Spearman rank correlation test. The results showed that most of the samples do not exclusively breastfeed their babies (59.6%), have less level of nutritional knowledge (46.8%), lack of energy and protein intake (87.2%) and (78.7%), physical activity level breastfeeding mothers classified as mild (76.6%), and the nutritional status (BMI) is not normal (46.8%). Statistical analysis showed there is association nutrition knowledge with breastfeeding mothers BMI(p = 0.005; p <0.05), energy and protein intake with breastfeeding mothers BMI (p = 0.001; p <0.05), and physical activity with breastfeeding mothers BMI (p = 0.030; p <0.05). The results showed knowledge of nutrition-related terms balanced nutrition for breastfeeding mothers still less (61.70%), so that need to increase knowledge of balanced nutrition for breastfeeding mothers who can contribute to improving nutrient intake, breastfeed mothers.